Nanocolumnar Pt:Ni Alloy Thin Films by High Pressure Sputtering for Oxygen Reduction Reaction. Issue 12 (16th December 2021) - Ergul-Yilmaz, Busra; Yang, Zhiwei; Basurrah, Assem O.; Perry, Mike L.; Reeves, Kimberly S.; Cullen, David A.; Karabacak, Tansel
Abstract : Self-supported nanocolumnar Pt:Ni thin films (TFs) with varying Pt:Ni atomic ratios and Pt mass loadings were produced on a microporous layer (MPL)-like surface composed of carbon particles by high pressure sputtering and examined as oxygen reduction reaction (ORR) electrocatalysts for polymer electrolyte membrane fuel cells. Cauliflower-like microstructures were observed from scanning electron microscopy imaging. Various Pt:Ni atomic ratios were obtained by simply changing the relative deposition power between Pt and Ni source and investigated by X-ray diffraction and quartz crystal microbalance analysis. Electrochemical characterization of the Pt:Ni-TF/MPL-like-layer/glassy-carbon samples was conducted through benchtop cyclic voltammetry and rotating disk electrode measurements. The electrochemically active surface area (ECSA) was found to be between 22–42 m 2 g −1 for different Pt:Ni atomic ratios. Lower Pt mass loadings exhibited a higher ECSA and the catalytic activity of all Pt:Ni ratios increased with the increase in Pt mass loading. The ORR activity of the Pt:Ni-TFs increased in the order of 3:1 < 1:1 < 1:3 with exhibiting a specific activity of 1781 μ A cm −2 and mass activity of 0.66 A mg −1 for the Ni-rich film with 1:3 ratio. The catalytic performance of Pt:Ni-TFs were higher than traditional high surface area carbon supported Pt nanoparticles, elemental Pt nanorods, and Pt-Ni nanorods.